Możliwości wykorzystania systemu satelitarnej detekcji podatkowej w podatku od nieruchomości, rolnym i leśnym - Namieciński, Bartosz (PRAWO i WIĘŹ, 2025)
The use of satellite data for faster and more efficient implementation of public administration tasks is one of the strategic goals of the Republic of Poland. This solution will undoubtedly allow for more efficient management of available resources, both financial and human, while at the same time reducing implementation costs. The purpose of the research was to verify the feasibility of using a satellite detection system for sealing the local tax system – In terms of real estate tax, agricultural tax and forestry tax. The study used the dogmaticlegal method of research, with the addition of the empirical-analytical method. Polish legislation and local laws were analysed and doctrinal and case law views were reviewed. In addition, information and statistical data provided by the Wroclaw City Hall were examined.